Inlet/outlet flow through various size of needle in the presence of magnetic field - Shah, Syed Saqib; ul Haq, Rizwan; Öztop, Hakan Fehmi; Raza, Ali (World Scientific Publ Co Pte Ltd, 2024)
Influence of Magnetohydrodynamics (MHD) on the fluid in channel flow in the presence of thin needle across the fluid movement is observed in this study. A two-dimensional computational analysis has been performed to see the effects of inlet/outlet conditions with inserted curvilinear shaped body in the channel. In this case, temperature on all boundaries is colder than that of inlet air and flat part of the inserted body. The governing equations are solved by using finite element method and magnetic field is also taken into account. With suitable dimensionless variables, PDEs are transformed into dimensionless PDEs, then raised parameter is simulated against the streamlines, isotherms and temperature distribution at mean position. Effect of Reynolds number, Richardson number, Magnetic hydrodynamic, size and state of needle is observed on local Nusselt number at the mean position. On isotherm profile, Reynolds number has a noticeable impact. With an increase in Re, heat circulation close to the needle increases, and for higher Ri, velocity on the outlet port increases. The inlet and outlet portions of the channel generate streamlines that have a significant impact on the diameter of the needle. Increased needle diameter causes heated lines to be pushed away from the centre. It is also found that the temperature gradient in the flow fields and heat transfer over the heated wall of the cavity are significant, altered by the placement of needle size during various computations.
Keywords: Thermal system; inlet/outlet; convection; MHD; finite element method